Aspectos constitucionais acerca da concilição no Processo Penal Brasileiro - Andrade Segundo, Arnaldo Pereira de (2018)
This paper deals with the constitutional aspects of conciliation in the Brazilian criminal procedure, especially the relationship between conciliation and the jury court in intentional crimes against life, in view of its constitutional provision for the prosecution of these crimes, as well as the correspondence of this type of resolution of conflicts with due process of law. The search for alternative means for conflict resolution is not new in the legal world, existing in Brazil in the civil sphere since the Philippine Ordinances in the XVII century and recently emphasizing the edition of the new Code of Civil Procedure of 2015. In this context, it is various legal institutes have demonstrated in the Brazilian criminal sphere, although they do not deal with an effective negotiation between prosecution and defense, they can be understood as an embryo of the subject in our legal system. In addition, it is the conciliatory experience in criminal matters in other countries, as a way to better understand it. It is also worth noting the examination of the draft of the new Code of Criminal Procedure with regard to conciliation. Finally, it also examines possible difficulties of current ordinary legislation, especially with regard to criminal enforcement and the role of the judge in the agreements